Treatment of Urinary Stones with Constitutional Homoeopathic Medicines—Two Evidence-Based Case Reports - Sahoo, Amulya Ratna; Hati, Akshaya Kumar; Nayak, Chintamani; Nayak, Chaturbhuja (Homœopathic Links, 2019)
Introduction Urolithiasis is a very common disease. Stones in any part of the urinary tract can produce symptoms and complication, but because the lower part of the ureter is the narrowest part of the urinary tract, stones get lodged easily producing pain and haematuria commonly. If we keep in mind the limitation and complication of the surgical procedure, homoeopathy can provide a real solution for such conditions. There are several ways of homeopathic prescription, such as based on keynotes, general symptoms, constitution, miasm, etc. Two cases of ureteric calculi are presented here, who were prescribed on the basis of constitutional symptoms and got good results.Case Profile In the first case, the only symptom was pain in the right flank, and as per ultrasonography (USG) report, there was 7.4 mm calculus in the lower part of the right ureter. In the second case, there were symptoms like pain in the left flank, burning urination and haematuria. The USG report confirmed 6 mm stone in the left ureterovesical junction (UVJ). After detailed case taking, both the cases were prescribed on the basis of constitutional symptoms. Lycopodium in 50 millesimal potencies (0/1–0/4) in the first case and Phosphorus in centesimal potency (1M) in the second case provided prompt relief of the symptoms within a short period. USG reports of both the cases also confirmed no stones after approximately 2 months of treatment.Conclusion Homeopathy provided good relief in two cases of ureteric calculi; constitutional medicines were found useful in combating acute ureteric colic and facilitating expulsion of stones. Because the constitutional symptoms matched, the polychrest homoeopathic medicines like Lycopodium and Phosphorus produced their best effect. But the inferences drawn from the two case reports may not be sufficient to reach a definitive conclusion. So clinical trials to establish the efficacy of constitutional remedies in the treatment of ureteric calculi are suggested.
Keywords: constitutional medicines; homoeopathy; lycopodium; phosphorus; ureteric calculi